PENGARUH PENGELUARAN PEMERINTAH, INVESTASI, DAN PENDIDIKAN TERHADAP PERTUMBUHAN EKONOMI DAN KESEJAHTERAAN MASYARAKAT KABUPATEN/KOTA PROVINSI BALI - Pradnyaswari, A.A Sagung Istri; Yasa, I Nyoman Mahaendra (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol 11 No 5 (2022): VOL 11 NO 5, MEI 2022 [1621-2044]DO - 10.24843/EEP.2022.v11.i05.p12, 2022)
Economic development distribution of economic growth and social welfare. Government spending, investment, education levels are all factors that influence this inequality. The purpose of this study to analyze, (1) government spending, investment, and education level directly on economic growth of districts / cities in Bali Province, (2) government spending, investment, education level and economic growth on the welfare of district / city communities in Bali Province, (3) the indirect effect of government spending, investment and the level of education on the welfare of the community through economic growth in districts / cities in Bali Province. Data used is secondary data from Bali Province Statistics Agency in 2014 - 2019 with path analysis method. The results showed that (1) government spending, investment and education level directly had positive significant effect on the economic growth of districts / cities in Bali Province (2) government spending, investment, education level and economic growth directly had positive significant effect on welfare District / city communities in Bali Province (3) government spending, investment and education levels do not have an indirect effect on community welfare through economic growth in districts / cities in Bali Province Keywords: government spending, investment, level of education, economic growth, community welfare